2010
DOI: 10.1108/10610421011086937
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory focus as a determinant of brand value

Abstract: PurposeThis research aims to investigate the relationship between consumer regulatory focus and brand value.Design/methodology/approachThree studies were conducted using both student subject pools and a broader sample from the US population. The relative chronic promotion or prevention orientation of each participant was measured, as was response to brand and pricing stimuli.FindingsPromotion‐oriented individuals are more sensitive to differences in established brands than prevention‐oriented individuals (stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…The top‐ and bottom‐ranked brands were recorded for use later in the survey. This task replicates the method for establishing high‐ and low‐tier brands used by Love et al (2010).…”
Section: Studymentioning
confidence: 81%
See 2 more Smart Citations
“…The top‐ and bottom‐ranked brands were recorded for use later in the survey. This task replicates the method for establishing high‐ and low‐tier brands used by Love et al (2010).…”
Section: Studymentioning
confidence: 81%
“…Price and perceived quality tend to be closely aligned within product categories, and the evaluation of price‐quality tiers in this paper is consistent with the approach used in prior research (cf. Lemon and Nowlis, 2002; Love et al , 2010; Nowlis and Simonson, 1996; Sethuraman et al , 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has identified that there are differences in terms of how individuals respond to branding (e.g. Love et al, 2010) and this was considered for potential relevance.…”
Section: Methodsmentioning
confidence: 99%
“…Limited research has been carried out exploring this aspect (e.g. Love et al,2010) but the tendency for empirical research to be reported at summary level has masked this as a possible influence.…”
Section: Interpretation Of Findingsmentioning
confidence: 99%